Constraints Faced by Potato Farmers in District Kannauj (U.P.) - Reema,; Awasthi, Nimisha; Singh, Poonam; Singh, A.K. (Indian Journal of Extension Education, 2020)
Potato has been considered to be one of the unavoidable necessities of life and it is demanded by the people belonging to all the classes of the society. The consumption of the potato has been rising at faster rate. Uttar Pradesh is the leading potato growing state in the country with a production of 9.93 million tonnes and Kannauj district leads in production but in respect of average production has 8th place in Uttar Pradesh, therefore, to know the constraints for lagging behind of the productivity of potato, present study was conducted in Jalalabad block and from Talgram block on 240 potato growers. Statements related to different constraints were framed and responses were recorded on three point Likert’s scale; Always, Sometimes and Never. Iimportant constraints always faced by maximum responded in cultivation was “lack of availability of sufficient good quality high yielding seed’, while in post harvest handling ‘lack of processing unit’ was maximum faced constraint, and in marketing ‘fluctuations of prices’ was major of constraints faced by farmers. The suggestions to overcome the problem of production were; reduced cost of fertilizer, supply of good quality of seed by government agencies at their door step and training regarding scientific potato production technology, post-harvest handling and processing.
Keywords: Constraints; Potato; Suggestions